Management and use of forest landscapes: Unpacking gendered knowledge and skills using participatory methods in forest genetic resources research, 8 - 12 July 2013, Yaoundé, Cameroon - Workshop Report - Basilio, C.; Fernández, M.E.; Bioversity International; International Support Group (2014)
This is the report of a participatory, learning-by-doing process, in which biophysical and social scientists engaged in Cameroon (July 2013), to strengthen their skills in gender-responsive participatory research. During the week-long workshop organized by Bioversity International’s Forest Genetic Resources Programme and facilitated by the International Support Group, participants practiced using various participatory research tools to unpack the gendered knowledge, skills and interests relevant to the management and use of forest genetic resources. The report can serve as a guide for training in gender-responsive participatory methods that generate quality research results and promote social learning, gender equity and the conservation of forest genetic resources.